2015
DOI: 10.1142/s0218348x15500176
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Fractal Model for Two-Phase Relative Permeability in Porous Media

Abstract: Multiphase flow in porous media is very important in various scientific and engineering fields. It has been shown that relative permeability plays an important role in determination of flow characteristics for multiphase flow. The accurate prediction of multiphase flow in porous media is hence highly important. In this work, a novel predictive model for relative permeability in porous media is developed based on the fractal theory. The predictions of two-phase relative permeability by the current mathematical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…It has been shown that the relative permeability curve should be a function of saturation and viscosity. 43 Therefore, the trend of relative permeability versus fluid viscosity is of theoretical significance. Figure 14 shows the significant influences of fluid viscosity ratio on the relative permeability.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that the relative permeability curve should be a function of saturation and viscosity. 43 Therefore, the trend of relative permeability versus fluid viscosity is of theoretical significance. Figure 14 shows the significant influences of fluid viscosity ratio on the relative permeability.…”
Section: Resultsmentioning
confidence: 99%
“…And the mobile fluid flow occurs in-between the boundary layer fluid. The boundary layer saturation is also known as the immobile phase saturation which can be written as 38,43…”
Section: Theoretical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section, the derived models are validated by comparing the calculated results to different experimental data sets. Firstly, a former model by Lei et al (2015) are selected to validate our derived relative permeability model with hydrate saturation S h = 0. Additionally, experimental results of K rw in HBS are also utilized to validate the relative permeability model in HBS.…”
Section: Validationmentioning
confidence: 99%
“…When the contact angle is higher than 90 • , the surface of hydrophobic material decreases the resistance of fluid flow, and the relative permeability correspondingly increases with the contact angle. Lei et al [26] proposed a fractal model for the prediction of gas-water relative permeability in fractures. They found that increasing the complexity of pore structure (fractal dimension) would result in a decrease of water relative permeability, while the gas relative permeability has a corresponding increase with the ratio of fluid viscosity.…”
Section: Introductionmentioning
confidence: 99%